2021
DOI: 10.1021/acs.est.1c06679
|View full text |Cite
|
Sign up to set email alerts
|

Decabromodiphenyl Ethane Mainly Affected the Muscle Contraction and Reproductive Endocrine System in Female Adult Zebrafish

Abstract: The novel brominated flame retardant decabromodiphenyl ethane (DBDPE) has become a widespread environmental pollutant. However, the target tissue and toxicity of DBDPE are still not clear. In the current study, female zebrafish were exposed to 1 and 100 nM DBDPE for 28 days. Chemical analysis revealed that DBDPE tended to accumulate in the brain other than the liver and gonad. Subsequently, tandem mass tag-based quantitative proteomics and parallel reaction monitoring verification were performed to screen the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 62 publications
(128 reference statements)
1
20
0
Order By: Relevance
“…Zebrafish has been extensively used for evaluating endocrine disruption and reproductive toxicity of xenobiotics in vertebrates due to its small size, ease of culture, short life cycle, and consistent egg production with high fertilization and hatching rates. 19 In fish, reproductive processes are regulated through coordinated interactions among steroid hormones along the HPG axis and through steroidogenesis of gonad organs. 20 Specifically, the hypothalamus releases gonadotropin-releasing hormone (GnRH) that stimulates the pituitary to secrete gonadotropin hormones, including follicle-stimulating hormone (FSH) and luteinizing hormone (LH).…”
Section: ■ Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zebrafish has been extensively used for evaluating endocrine disruption and reproductive toxicity of xenobiotics in vertebrates due to its small size, ease of culture, short life cycle, and consistent egg production with high fertilization and hatching rates. 19 In fish, reproductive processes are regulated through coordinated interactions among steroid hormones along the HPG axis and through steroidogenesis of gonad organs. 20 Specifically, the hypothalamus releases gonadotropin-releasing hormone (GnRH) that stimulates the pituitary to secrete gonadotropin hormones, including follicle-stimulating hormone (FSH) and luteinizing hormone (LH).…”
Section: ■ Introductionmentioning
confidence: 99%
“…Although it is evident that neonicotinoids can cause adverse effects on vertebrates, these studies were mainly conducted over short-term periods (e.g., <10 d). , It is largely unknown whether long-term exposure (e.g., from juvenile to adult) to neonicotinoids at environmentally relevant concentrations will detrimentally influence vertebrates. Zebrafish has been extensively used for evaluating endocrine disruption and reproductive toxicity of xenobiotics in vertebrates due to its small size, ease of culture, short life cycle, and consistent egg production with high fertilization and hatching rates . In fish, reproductive processes are regulated through coordinated interactions among steroid hormones along the HPG axis and through steroidogenesis of gonad organs .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few studies on the biological toxicity of DBDPE have found that DBDPE has thyroid toxicity, hepatotoxicity, cardiovascular toxicity, and endocrine toxicity 7,15,25–29 . Studies showed that DBDPE disturbed thyroid hormone homeostasis 7,25,26 .…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, a few studies on the biological toxicity of DBDPE have found that DBDPE has thyroid toxicity, hepatotoxicity, cardiovascular toxicity, and endocrine toxicity. 7,15,[25][26][27][28][29] Studies showed that DBDPE disturbed thyroid hormone homeostasis. 7,25,26 Tian Chen et al reported that serum DBDPE concentration was positively correlated with total triiodothyronine and total thyroxine serum levels of adults in DBDPE-producing areas in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation